2013
DOI: 10.1128/aac.00105-13
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Effects of Caspofungin against Two Yeast Species, Saccharomyces cerevisiae and Candida albicans

Abstract: Saccharomyces cerevisiae and Candida albicans are model yeasts for biotechnology and human health, respectively. We used atomic force microscopy (AFM) to explore the effects of caspofungin, an antifungal drug used in hospitals, on these two species. Our nanoscale investigation revealed similar, but also different, behaviors of the two yeasts in response to treatment with the drug. While administration of caspofungin induced deep cell wall remodeling in both yeast species, as evidenced by a dramatic increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 47 publications
(38 reference statements)
11
78
0
Order By: Relevance
“…4) and those described previously by El-Kirat-Chatel and Dufrene (27) and Formosa et al (29). In addition, we also observed that our mutants exhibited decreased elasticity, which again is similar to what was observed for caspofungin treatment by Formosa et al (29).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…4) and those described previously by El-Kirat-Chatel and Dufrene (27) and Formosa et al (29). In addition, we also observed that our mutants exhibited decreased elasticity, which again is similar to what was observed for caspofungin treatment by Formosa et al (29).…”
Section: Discussionsupporting
confidence: 78%
“…By pressing the cantilever tip against the surface of the cell, differences in both surface elasticity (30)(31)(32)(33) and indentation (34,35) can be measured. Previous studies reported that wild-type C. albicans cells treated with caspofungin have decreased surface elasticity (Young's modulus) compared to that of untreated cells (29). However, other work has shown that surface elasticity is increased compared to that of wild-type cells following treatment with caspofungin (36).…”
mentioning
confidence: 75%
See 3 more Smart Citations